Religiosity, Marijuana Use, and Binge Drinking: A Test of the Moral Community Hypothesis. (23rd January 2018) - Rivera, Craig J; Lauger, Timothy R; Cretacci, Michael A
Abstract: We use data from Wave 3 of the National Study of Youth and Religion (NSYR), a nationally representative study of adolescents and emerging adults, to examine the association between religiosity and marijuana use and binge drinking, as well as the importance of social context for these associations. Specifically, we test the moral community hypothesis, originally stated by Stark and colleagues, using a micro-level conceptualization of moral community. We find that higher levels of religiosity are associated with lower odds of engaging in both marijuana use and binge drinking, and that an individual's level of integration into a moral community moderates the association between religiosity and both outcomes. Implications of our findings are discussed.